Perlindungan Hukum dan Risiko Investasi pada Securities Crowdfunding Syariah: Analisis Maslahah Mursalah (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2025)
This study aims to analyze legal protection and investment risks in Sharia Securities Crowdfunding (SCF) using the perspective of maslahah mursalah as the basis for assessment. The methodology employed is qualitative library research with a normative legal study approach, utilizing primary sources in the form of legislation, DSN-MUI fatwas, and OJK regulations, as well as secondary sources in the form of relevant academic journals and books published within the last ten years. The findings indicate that legal protection for investors in Sharia SCF already has a normative foundation through OJK Regulation No. 57/POJK.04/2020 and DSN-MUI Fatwa No. 140/DSN-MUI/VII/2021, but its implementation still faces challenges in terms of supervision, information transparency, and the effectiveness of dispute resolution mechanisms. The maslahah mursalah analysis affirms that Sharia SCF is permissible as long as it upholds the principles of justice, trustworthiness, and benefit, thereby necessitating strengthened regulations and oversight to optimally achieve the goal of investor protection.